2019
DOI: 10.1111/his.13889
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene expression profiling and biomarkers between histological colorectal carcinoma subsets from the serrated pathway

Abstract: Aims To discern the differences in expression profiling of two histological subtypes of colorectal carcinoma (CRC) arising from the serrated route (serrated adenocarcinoma (SAC) and CRC showing histological and molecular features of a high level of microsatellite instability (hmMSI‐H) both sharing common features (female gender, right‐sided location, mucinous histology, and altered CpG methylation), but dramatically differing in terms of prognosis, development of an immune response, and treatment options. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition, gene expression profiling was carried out in order to clarify the role of the immune response between the two end results of the serrated pathway. As a result, a higher expression of ICAM1 , an adhesion molecule involved in cellular immune responses, and a lower expression of CRCP and CXCL14 were identified in SAC versus hmMSI-H CRCs [132].…”
Section: Serrated Adenoma To Carcinoma Sequence: Initiation and Prmentioning
confidence: 99%
“…In addition, gene expression profiling was carried out in order to clarify the role of the immune response between the two end results of the serrated pathway. As a result, a higher expression of ICAM1 , an adhesion molecule involved in cellular immune responses, and a lower expression of CRCP and CXCL14 were identified in SAC versus hmMSI-H CRCs [132].…”
Section: Serrated Adenoma To Carcinoma Sequence: Initiation and Prmentioning
confidence: 99%
“…These methods are expanded versions of descriptions in our related work 11,45 . Total RNA was quantified by spectrometry (NanoDrop ND1000, NanoDrop Technologies, Wilminton, DE) and fragment size distribution was analysed by RNA 6000 Pico Bioanalyzer assay (Agilent Technologies, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…These genes, along with CXCL14, are upregulated in SAC compared to hmMSI-H, although the cell of origin for this overexpression is elusive, as these genes are normally expressed in myeloid cells, which are not as abundant in SAC as they are in CC or hmMSI-H [27]. ICAM1, however, is more expressed in hmMSI-H than in SAC, which typically favors antigen presentation, is associated with less risk of metastases and is related with a good prognosis due to its association with leukocyte extravasation and improved immune response in the tumor microenvironment [6]. The study of the microtranscriptome has shown a difference in the expression of miR-181-a2, which is lower in SAC than in hmMSI-H.…”
Section: Sac Is Especially Capable Of Avoiding the Immune Responsementioning
confidence: 99%
“…Less is known about the serrated pathway, in which a high level of microsatellite instability (MSI-H), high frequency of BRAF mutation and the CpG island methylation phenotype (CIMP) seem to be the leading carcinogenic causes, although significant proportions of SAC are KRAS-mutated and microsatellite-stable [2,3]. These alterations contribute to the development of serrated adenocarcinoma (SAC) and the CRC showing histological and molecular features of MSI-H (hmMSI-H) [4], which are considered as endpoints of this pathway [5,6]. MSI-H is a manifestation of a deficiency in DNA mismatch repair mechanism which has been associated with histological features including the presence of signet-ring cells, mucine, tumor heterogeneity with a medullary component, poor differentiation, "pushing" type tumor growth pattern, peri-and intra-tumoral infiltrating lymphocytes, and "Crohn-like" inflammatory response [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation